2002
DOI: 10.1007/s00213-002-0999-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies in patients with major depression not responding to first-line sertraline treatment

Abstract: After 6 weeks of insufficient antidepressant treatment with 50-100 mg/day sertraline, a continued treatment with 100 mg/day sertraline can be considered until at least week 8 before considering changing strategy, unless the condition deteriorates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(23 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…Of the 7 included RCTs, 2 investigated pharmacotherapy with fluoxetine ( n = 448) [21,22], sertraline ( n = 272) [23,24], and paroxetine ( n = 146) [25,26], whereas 1 study examined duloxetine ( n = 255) [27] and maprotiline ( n = 87) [25]. In the individual trials, the number of participants ranged from 60 [26] to 371 [21] (mean = 151.0 ± 112.9 patients), and trial duration varied between 3 [25] and 8 weeks [27] (mean = 5.0 ± 1.6 weeks).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 7 included RCTs, 2 investigated pharmacotherapy with fluoxetine ( n = 448) [21,22], sertraline ( n = 272) [23,24], and paroxetine ( n = 146) [25,26], whereas 1 study examined duloxetine ( n = 255) [27] and maprotiline ( n = 87) [25]. In the individual trials, the number of participants ranged from 60 [26] to 371 [21] (mean = 151.0 ± 112.9 patients), and trial duration varied between 3 [25] and 8 weeks [27] (mean = 5.0 ± 1.6 weeks).…”
Section: Resultsmentioning
confidence: 99%
“…The number needed to treat (NNT) for the combination was 4 patients for 1 remission beyond what would be expected for fluoxetine alone. A more recent RCT has shown that adding mianserin to sertraline nonresponders offered no advantage over adding placebo [50]. However, the initial trial of sertraline monotherapy was brief and a dose increment of sertraline was carried out 2 weeks prior to randomization, thereby confounding the interpretation of the results.…”
Section: Resultsmentioning
confidence: 99%
“…The remission rate was also over twice as great in the mianserin+fluoxetine group vs the placebo+fluoxetine group (Ferreri et al, 2001). A recent double-blind study (mianserin+sertraline vs placebo+sertraline) failed to observe beneficial effects of adding mianserin (30 mg/day) to sertraline (100 mg/day) in patients failing to respond to an initial open 6-week treatment with sertraline (50 mg/day  4 weeks; 100 mg/day  2 weeks; Licht and Qvitzau, 2002). Differences in depression severity may have contributed to these differences.…”
Section: Mirtazapine and Mianserin: Clinical Activity In Major Depresmentioning
confidence: 99%
“…Differences in depression severity may have contributed to these differences. The 17-item HAM-D scores required for study entry was X25 for the fluoxetine augmentation study after initial fluoxetine treatment (Ferreri et al, 2001), whereas the entry criterion was X18 for the sertraline augmentation study before the initial sertraline treatment (Licht and Qvitzau, 2002).…”
Section: Mirtazapine and Mianserin: Clinical Activity In Major Depresmentioning
confidence: 99%